Poverty and deprivation in Europe - Nolan, Brian; Whelan, Christopher T. (Oxford ; New York : Oxford University Press, 2011)
This text combines a focus on multidimensionality with a comparative approach to survey the role of non-monetary indicators of deprivation. It shows how poverty varies across countries and over time, who is affected, and which groups should be targeted in framing anti-poverty strategies.
Oxford scholarship online Economics and Finance
Includes bibliographic references and index.
roy
Keywords: Poverty -- European Union countries; Poor -- European Union countries; Cost and standard of living -- European Union countries